P579 High prevalence and correlates of syphilis and HIV infection among adolescents of the comarca ngäbe-buglé, panama. (14th July 2019) - Gabster, Amanda; Pascale, Juan; Cislaghi, Ben; Martinez, Alexander; Ortiz, Alma; Castillo, Jorge; Herrera, Mellissa; Herrera, Genarino; Gantes, César; Quiel, Yaremis; Ríos, Adan; Campbell, Eliris; et al.
Abstract : Background: The Comarca Ngäbe-Buglé (CNB), situated in western Panama, is home to over 200, 000 indigenous peoples; the region has the highest levels of multidimensional poverty in the country. The prevalence and correlates of syphilis and HIV have not been previouslydescribed among adolescents of CNB. Methods: A cross sectional study, using multistage cluster sampling design with equal probability of selection and random sampling of clusters, among male and female participants aged 14–19 years, was conducted in 10 high schools in CNB from July-November 2018. A questionnaire was self-administered, participants provided blood, as well as urine and self-administered cervical/vaginal swabs for STI testing (data not shown). Serum was tested for HIV using rapid test/viral load confirmation; syphilis using TPPA/VDRL confirmation for active syphilis. Results: A total of 316 female adolescents and 384 males participated. A history of sexual activity was reported by 76.0% of females and 78.3% of males; forced sexual intercourse by 29.0%(86/297) of females and 15.1%(55/364) of males; transactional sex (being offered money, food, housing, transport in exchange for sex) by 14.6%(43/295) of females, 12.3%(45/365) of males. Of sexually experienced participants, 4.7%(25/535) had a confirmed HIV (1 female, 3 males) or active syphilis (3 females, 19 males) test. Correlates of either HIV/syphilis infection include: male gender (AOR=4.4, 95%CI: 1.5–13.1) and having been offered transactional sex (AOR=3.3, 95%CI: 1.3–8.0). Among males only, 4/26 (15.4%) of those who reported same-sex sexual intercourse (MSM) tested positive for syphilis. Correlates of HIV/syphilis among all male participants included transactional sex (AOR=2.7, 95%CI: 1.0–7.9), having been forced to have sex (OR=2.6, 95%CI: 1.0–6.9) and MSM (OR=2.7, 95%CI: 0.9–8.9). Conclusion: There is very high syphilis and HIV prevalence among high-school-going indigenous adolescents of CNB, particularly among males. Transactional sex and forced sex are driving factors. Targeted interventions should include prevention education, testing and treatment, especially for boys reporting homosexual sex. Disclosure: No significant relationships.